Determination of Pozzolanic activity of Buffalo Dung Ash to utilize as cement replacement material in concrete - Mashood Rehman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Increasing construction activity around the globe has raised the demand for cement to 4.4 giga-tonnes/year, making it costlier, and its consumption second to water. Meanwhile, a tonne of clinker produces a tonne of CO2 on a large consumption of natural resources of raw materials and energy of 10–11 EJ/year, which is why an affordable and environmentally sustainable substitute for cement is needed today. Pakistan possesses more than 30 million buffalos. Each can produce up to 15 kg of dung per day, resulting in 450 million kg of dung produced in Pakistan alone. This research aims to investigate the pozzolanic activity of Buffalo dung ash and determine the optimum conditions for developing the ash, along with the optimum dosage as cement replacing material in Normal concrete. For this purpose, five buffalo dung ash samples were prepared by calcining the dung in a muffle furnace for a 1-hour duration at 400°C, 500°C, 600°C, 700°C, and 800°C, and after cooling, sieving through a No. 100 sieve. The Strength Activity Index was determined as per ASTM C311. The results showed that developed ash at 600oC has a maximum Strength Activity Index of 94.2%, meeting the ASTM C618 standards for pozzolanic material, which was further confirmed by X-ray Fluorescence analysis. Furthermore, when 5%, 10%, 15%, and 20% of this ash were used as cement substitutes in concrete, the compressive strength increased by 11.2% on 10% substitution compared to the control mix. Based on the parameters investigated, it was found optimal to replace 10% of the cement in the concrete with buffalo dung calcined at 600°C for 1 hour.